Awakening Games Genre of Lithuanian Dancing Folklore: the Aspects of Education and Therapy - Zvicevičienė, Solveiga; Aleksienė, Vilmantė (Pedagogika, 2015)
Lithuanian folk awakening games for babies and young age children are classified as dancing folklore genre. These are syncretic musical compositions of low volume, intended for infants and small children, which are performed vocalising and in action. This is child-friendly interactive action, which has a playful nature and is based on intensive movement. A rich range of possibilities is noticeable in Lithuanian folk awakening games, necessary for versatile child’s education / learning. Purpose of article: to disclose the application possibilities of awakening games in work with children, who have special needs: 1) achieving the training goals; 2) achieving the therapeutic goals. Research method: analysis suitability of children awakening games for education and therapy. Literature of different areas has been reviewed: ethnic culture, music therapy, dance-movement therapy, ethno therapy, developmental psychology, education and special education. It is also based on manuscripts material from the Archives: of Lithuanian Folk Culture Centre, Institute of Lithuanian Literature and Folklore, Ethnomusicology Archive of Lithuanian Academy of Music and Theatre and on its expedition manuscripts material as well. Drawn conclusions: Lithuanian folk awakening games belong to minor genre of dancing folklore, which is expressed in syncretic musical compositions of low volume, has “encoded”, not yet been researched, broad options of educational and therapeutic content, and can be purposefully used trying to respond to various individual or special needs of a child. Awakening games can be used in a child‘s education / self-training process for numerous, complementary factors, which stimulate development of a child: training of communication and language, promotion of environmental knowledge and acceptance of changes, shaping of positive behaviour, training of motility, development of playfulness and creativity skills. Lithuanian folk awakening games can be used in therapeutic process as an effective means of communication formation with a child and activation of its ability to imitate. While playing with a child, conditions are created naturally for its psychological security, self-esteem and confidence; self-expression, self-realization; reducing of its fears; relaxation and experience of pleasure and other. Awakening games are still important in contemporary culture for versatile child’s development / self-formation and recommended to apply in Lithuanian families, as well as in working methodologies of a special educator, physical therapist, speech therapist, ergotherapist, psychologist and art therapist.